PENGARUH STRATEGI PROMOSI JABATAN, PEMBERIAN KOMPENSASI DAN DISIPLIN KERJA DALAM MENINGKATKAN KINERJA PERSONEL POLRES PAMEKASAN - Arief Kurniady; Nugroho Mardi W; Indra Prasetyo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 85 personnel. The objectives of this study are 1). To prove and analyze whether promotion, compensation, work discipline simultaneously has a significant influence on the performance of Pamekasan Police personnel. 2). To prove and analyze whether promotion has a significant effect on the performance of Pamekasan Police personnel. 3.) To prove and analyze whether the provision of compensation has a significant effect on the performance of the Pamekasan Police personnel. 4.) To prove and analyze whether work discipline has a significant effect on the performance of Pamekasan Police personnel. The results showed that 1.) Job promotion, compensation and work discipline simultaneously had a significant effect on improving the performance of Pamekasan Police personnel. 2.) Promotion has a significant effect on improving the performance of Pamekasan Police personnel. 3.). The provision of compensation has a significant effect on improving the performance of the Pamekasan Police personnel. 4.) Work discipline has a significant effect on improving the performance of the Pamekasan Police personnel.